2023
DOI: 10.3389/fonc.2023.1124592
|View full text |Cite
|
Sign up to set email alerts
|

Dosiomics and radiomics to predict pneumonitis after thoracic stereotactic body radiotherapy and immune checkpoint inhibition

Abstract: IntroductionPneumonitis is a relevant side effect after radiotherapy (RT) and immunotherapy with checkpoint inhibitors (ICIs). Since the effect is radiation dose dependent, the risk increases for high fractional doses as applied for stereotactic body radiation therapy (SBRT) and might even be enhanced for the combination of SBRT with ICI therapy. Hence, patient individual pre-treatment prediction of post-treatment pneumonitis (PTP) might be able to support clinical decision making. Dosimetric factors, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Due to the high morbidity and potential mortality of RP in radiotherapy for thoracic tumors, it is particularly important to explore e cient and convenient predictive variables to reduce the incidence of RP and mitigate radiotherapy toxicity. Clinical parameters [15] , cytokines [16] , and dosimetric parameters [17] have been used in previous studies for prediction, which have poor predictive e cacy and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high morbidity and potential mortality of RP in radiotherapy for thoracic tumors, it is particularly important to explore e cient and convenient predictive variables to reduce the incidence of RP and mitigate radiotherapy toxicity. Clinical parameters [15] , cytokines [16] , and dosimetric parameters [17] have been used in previous studies for prediction, which have poor predictive e cacy and stability.…”
Section: Discussionmentioning
confidence: 99%
“…57 After the high radiation dose of radiotherapy (RT), incidence of ICI-pneumonitis increased. 58 Besides, the history of chronic lung disease, such as interstitial lung disease, especially lung fibrosis, chronic obstructive pulmonary disease (COPD) and asthma, was independently associated with an increased incidence of ICI-pneumonitis. 51,59,60 Thomas HMT et al…”
Section: Risk Factorsmentioning
confidence: 99%
“…Combination therapy with ipilimumab plus nivolumab resulted in the highest incidence of pneumonitis (5%–10%), and 2% were reported to be Grade 3 or 4 events 57 . After the high radiation dose of radiotherapy (RT), incidence of ICI‐pneumonitis increased 58 . Besides, the history of chronic lung disease, such as interstitial lung disease, especially lung fibrosis, chronic obstructive pulmonary disease (COPD) and asthma, was independently associated with an increased incidence of ICI‐pneumonitis 51,59,60 .…”
Section: Ici‐pneumonitismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of treatment plan physical quantities including skin dose distribution and dose volume histograms (DVHs) [ 7 , 8 ], as well as patient’s demographic and clinical characteristics have been investigated in predicting AST in breast RT by several investigators [ 9 , 10 ]. However, DVHs lack spatial information of the dose of treatment plans [ 11 ]. A recent literature review of 38 studies has shown considerable heterogeneity in assessing acute radiation dermatitis and contributing risk factors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%